(3EYQGH OjHGLI GdeUHGM aj ahGFO ZQGFH GdeaJGMs ((3CMeO Hf YKeGf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjHdZ cfgg LGO hdG jMUi YOO fYeg YGO CeG HYO agPg ChQGb GdEYQGH OjHGLI GdeUHGM ai ahGFO ZQGFH GdeaJGM s
(3BNQgG (B:s
(3bdfG gPG GdSDGd YGe ai cd MUQ LYdi dGYbdi dcf jfOaY Pdc HGdESJbQGA jYfi EPG de jcf GdHMK ef LgI GdYGedjI jdRe KHhJ GdNGeS HGdESJbQGA dG HGdYbd dCf GdYbd jLhR Cf jchf TjFkG BNQ ZjQ GdNGeS Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdfMhs